Effect of deep breathing training on exercise - induced changes in electrocardiogram (ecg) of the young normal volunteers - Mee, Jong Shun (2004)
The aim of this study was to investigate the effect of deep breathing training on exercise - induced changes in electrocardiogram {ECG) in normal healthy volunteers. Subjects were divided into two groups - experimental group and control group. The subjects from experimental group were asked to practice deep breathing exercise for 15 minutes twice a day for consecutive 3 week periods with different timing each week; while control group did not do deep breathing exercise. The ECG (lead II) was recorded before and after performance of physical exercise in cycle ergometer with 40 - 50 rpm and 20 Newton resistances for 5 minutes. The results show that, the amplitude of R wave increased in experimental group and control group before physical exercise (p < 0.011) and the R wave amplitude increased further after physical exercise only in experimental group (p <0.001 ). The amplitude of P wave increased significantly (p < 0.003) after physical exercise in both the groups, but there was no difference in the increase between the control and experimental group. The amplitude of T wave was increased significantly after physical exercise in both the groups (p < 0.001 ). The mean values show that the increase in amplitude of T wave is more in control group than in the experimental group. The duration ofT wave and RR interval was decreased after physical exercise, and the decrease was similar in both the groups. Other parameters did not show any significant change in both the groups.The more increase in the amplitude of R wave and less increase in the amplitude of T wave in experimental group indicate that the deep breathing training improves cardiac performance to cope up with the exercise stress.